Strategic Leadership for Emerging Economies: Building Agile Higher-Education Institutions in Caribbean Countries - Paul (Sr.), Stanley Anthony Vivion; Joseph, Justin; Paul (Jr.), Stanley Anthony Vivion; McDonald, Coretta; Solomon, Orande Kenneatior; Rambhajan, Shenelle (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
The accelerating pace of economic transformation across Caribbean countries has generated an urgent need for agile, forward-looking higher-education institutions capable of anticipating market shifts, responding to new knowledge demands, and developing a competitive 21st-century workforce. Strategic leadership has emerged as a central mechanism for institutional agility, particularly in small developing countries where resource constraints, demographic pressures, and technological disparities pose structural challenges. This article critically examines strategic leadership practices within higher-education systems in the Caribbean, with specific reference to Guyana. Drawing on contemporary leadership theory, organizational-change literature, and regional development frameworks, the article identifies core competencies necessary for institutional adaptability, including anticipatory governance, data-driven decision-making, cultural responsiveness, stakeholder integration, and innovation capacity. A conceptual model for agile higher-education leadership in emerging economies is proposed, followed by implications for policy, governance, and institutional development.